Ikhtilaf sebagai Sumber Radikalisasi : Pemahaman dan Solusi untuk Mencegah Ekstremisme dalam Perspektif Islam - Arindy, Aisyah Dwi Cahaya (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Disagreement or differing opinions is an inseparable part of the intellectual dynamics in Islam, which has been recognized and respected as a blessing from the very beginning. Although disagreement has the potential to enrich religious understanding and broaden theological perspectives, in certain social and political contexts, these differences are often exploited for radical purposes that can foster extremism and division among Muslims. In this journal, the author analyzes how disagreement, which should serve as a means to develop inclusive and moderate thinking, can be misused as a gateway to the radicalization of thought and violence. By referring to the fundamental principles of the Quran , Hadith, and qiyas,  this article aims to reveal a theological framework that can help Muslims understand and manage differences wisely. Furthermore, this journal also provides a practical approach that can be applied by scholars and the general public to prevent radicalization that comes from ikhtilaf by prioritizing the values of moderation (tawasuth) and tolerance (tasamuh) in accordance with Islamic teachings. Through a deeper understanding of ikhtilaf, it is hoped that Muslims can maintain unity and harmony without sacrificing freedom of opinion in a constructive framework.